Survey On Argo UML Tool (International Journal of Engineering and Computer Science, 2017)
ArgoUML is an UML diagramming application written in Java and released under the open source Eclipse Public License. By virtue of being a Java application, it is available on any platform supported by Java. Within the open-source community, ArgoUML represents a major cooperative effort for the development of a UML development environment, ArgoUML is still under development, and processing errors arise periodically.